An Analysis of Code Mixing Used by English Department Students of Universitas Riau on Instagram - Dewi Fatimah; Eliwarti; Novitri (JEE (Journal of English Education), 2021)
This study has an objective to find out the code mixing types used in Instragram bythe English Department students -Universitas Riau. The respondents of thisresearch were all related students in2016/2017 academic year. The researcherused descriptive qualitative research design and the data were collected from documents as the instrument. Then, Hoffman‟s theory (1991) was used for data analysis to find out the types of code mixing used by these students. Thus the research finding has revealed that all of the three types of code mixing appearedin the captions or comments written by the students as suggested by Hoffman. There were twenty-nine data classified into intra- sentential, two data classified into intra-lexical code mixing, two data classified into involving a change of pronunciation and two data classified into both intra-sentential code mixing and intra- lexical code mixing. Key Words: Analysis, Code Mixing, Instagram.